La comunicación digital y los rasgos de personalidad en los estudiantes de la Unidad Educativa Rafael Vásconez Gómez - Enriquez Acosta, Selene Jael (2019)
In these times, the product of globalization and the advancement of digital media, has allowed the emergence of the internet, since its ease of handling and versatility in a few years has exceeded the limits of the unimaginable, increasing the amount of users who access the network and who benefit from its enormous variety of services. The large set of information that can be accessed contains almost all the knowledge and hobbies of human work, therefore, it has been called the great library of humanity. The research was carried out in the manner described below: background, problem statement, problem formulation, delimitation, general and specific objectives, and finally its justification, and at the same time, the topics of the theoretical framework are included: What are the digital media ?, Types of activities that are established on the Internet ?, Internet addiction ?, Personality deficit, self-esteem, deficit in interpersonal relationships: shyness and social phobia shyness, types of phobias, cognitive deficits: scattered attention and displaced, psychopathological alterations. In the practical part a bibliographic and documentary research is carried out that will theoretically sustain the work carried out, later the methodology used for this research is described, the analysis and interpretation of the results of the surveys taken to teachers and students is detailed. The conclusions and recommendations are pointed out.